Dinamika Gerakan Pembaharuan Islam di India dan Pakistan (Studi Historis dan Pemikiran Tokoh-Tokohnya) - Rulita Patriani; Riko Riko; Farki Azhar; Julida Sari; Rina Setyaningsih (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The Islamic reform movement in India and Pakistan arose as a response to the social, political, and intellectual challenges faced by Muslims during colonial times and the early years of Pakistan’s formation. This study explores the key drivers behind the movement and highlights the contributions of figures such as Sayyid Amir Ali, Muhammad Iqbal, and Muhammad Ali Jinnah in promoting education, critical thinking, and social change. The movement successfully fostered renewal while preserving religious values, maintaining its relevance in the ongoing evolution of modern Islam.